Somatotype of elite rhythmics gymnasts: a systematic review - Pencic, N.; Spasic, A.; Purenovic-Ivanovic, T. (XX Scientific Conference.FIS COMMUNICATIONS 2017" in physical education, sport and recreation (Nis, Serbia, october 19-21st, 2017), 2017)
The somatotyping method has an essential importance in sports where the body constitution can directly affect the biomechanics of movement as well as the results of performance. Belonging to group of aestethics sports, for rhythmics gymnastics this method is very important. The aim of this study was to systematicly investigate the adequate literature to determine the type of somatotipe of elite rhythmics gymnasts junior and senior categories. Inclusion criteria were studies that were assesing anthropometrics caracteristics of elite rhythmics gymnasts (body height, body weight, body mass, body mass index) , as well as the studies that were determining somatotypes of elite rhythmics gymnasts based on anthropometrics characteristics. Nine studies completed the criteria for inclusion in this systematic review. Based on the results it can be concluded that overwhelming somatotype in rhythmics gymnastics is meso-ectomorph. Further evidence is necessary in order to confirm the results completely.